HIV/AIDS, beersellers and critical community health psychology in Cambodia: A case study. (January 2014) - Lubek, Ian; Lee, Helen; Kros, Sarath; Wong, Mee Lian; Van Merode, Tiny; Liu, James; McCreanor, Tim; Idema, Roel; Campbell, Catherine
This case study illustrates a participatory framework for confronting critical community health issues using 'grass-roots' research-guided community-defined interventions. Ongoing work in Cambodia has culturally adapted research, theory and practice for particular, local health-promotion responses to HIV/AIDS, alcohol abuse and other challenges in the community of Siem Reap. For resource-poor communities in Cambodia, we recycle such 'older' concepts as 'empowerment' and 'action research'. We re-imagine community health psychology, when confronted with 'critical', life-and-death issues, as adjusting its research and practices to local, particular ontological and epistemological urgencies of trauma, morbidity and mortality.